Domoic acid binds iron and copper: a possible role for the toxin produced by the marine diatom Pseudo-nitzschia - Rue, E.; Bruland, K. (Marine Chemistry, 2001)
Toxigenic species of the pennate diatom Pseudo-nitzschia can produce domoic acid (DA), an analog of the excitatory neurotransmitter glutamate and known to cause the human illness amnesic shellfish poisoning (ASP). Although the trophic transfer of this phycotoxin resulting in mass marine bird and mammal mortality has recently been demonstrated, the physiological role of domoic acid to the causative organism is still unknown. Domoic acid is a small tricarboxylate amino acid whose structure resembles that of known iron-complexing agents produced by terrestrial plants, such as mugineic acid. This similarity in chemical structure of domoic acid to other phytosiderophores suggests a role for domoic acid as a trace metal chelator. Using a highly sensitive adsorptive cathodic stripping voltammetric technique, we investigated the iron and copper-binding characteristics of domoic acid revealing it does form chelates with both iron and copper and with the following conditional stability constants: K-FeDA,Fe(III)’(cond) = 10(8.7 +/- 0.5) M-1 and K-CuDA,Cu(II)’(cond) = 10(9.0 +/- 0/2) M-1 (K-FeDA,Fe3+(cond) = 10(18.7 +/- 0.5) M-1 and K-CuDA, Cu2+(cond) = 10(10.3) +/- M-1). Certain Pseudo-nitzschia species may therefore produce domoic acid selectively bind trace metals in order to either increase the availability of an essential micronutrient, such as in the case of iron, or to decrease the availability of a potentially toxic trace metal, such as in the case of copper. The strength with which domoic acid binds iron and copper in seawater combined with concentrations of dissolved domoic acid potentially produced and released during toxic bloom conditions render dissolved iron and copper sufficiently bound to domoic acid in seawater so as to affect their chemical speciation and thus their biological availability. In addition, domoic acid may be particularly important in solubilizing particulate iron suspended in these coastal waters where Pseudo-nitzschia blooms tend to occur. Thus, possible physiological roles for domoic acid with respect to the harmful algal species Pseudo-nitzschia may include the acquisition (iron) or detoxification (copper) of trace metals in seawater. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: atlantic-ocean; blue-green; cathodic stripping voltammetry; complexation; domoic acid; harmful algal species; hydroxamate-siderophore; iron and copper biological availability; mugineic acid; natural organic-ligands; north pacific; possible phytosiderophore; seawater